(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Covid-19 infection is very dangerous and its complications can be severe, so vaccination against infection is the most effective way. Several vaccines have been developed to combat the infection, but their effectiveness varies. For this reason, only highly effective and safe vaccines are used to prevent infection.